Farrowing Induction in Swine with Prostaglandin: Effect on Farrowing Traits and Piglet Performance - Singh, Mahak; Mollier, Rongsennangba Talimoa; Patton, Renphamo Nzanthung; Katiyar, Rahul; Deori, Sourabh; Singh, Gyan Dev; Kalita, Homeswar; Mishra, Vinay Kumar (The Indian Journal of Animal Reproduction, 2023)
The variation of gestation length in sows leads to difficulties performing farrowing supervision in commercial farms. The present study determined the efficacy of prostaglandin F2alpha (PGF2α) administration on induction of farrowing in pig. The sows (n=50) were randomly divided into two groups. In group-1, sows (n=25) were injected with placebo intramuscularly (one mL sterile water) on 113th day of gestation at 8.00 am in the morning. In group-2 (n=25), cloprostenol sodium (250 mcg) was injected intramuscularly on 113th day of gestation at 8.00 am in the morning. The parameters recorded during the experiment were gestation length, farrowing duration, total number of piglets born per litter (NTB), number of piglets born alive per litter (NBA), number of stillborn per litter, mummified foetuses per litter, birth interval (min), number of piglets alive at day 3 of lactation and piglet mortality (%) till day 3 of lactation. Gestation length was significantly (p0.05). The PGF2α administration also resulted in increased proportion of sows that farrowed on day 114 of gestation. In conclusion, PGF2α administration on day 113 of gestation could be an option for controlled farrowing in sow without any adverse effects.
Keywords: Sow; Prostaglandin; Farrowing induction; Farrowing traits; Piglet performance